Applying Decisions' Theory to choose an Alternative Factor for Spatial Development in Holy Karbala Governorate - Zahraa Mohammed Jasim; Mohammed Jasim Sha'ban (College of Education for Women, 2023)
It is very well known in the planning publications that when creating spacing development to a region or sub-region, it can be able to make more than an alternative consisting with the strategic directions overtaken from the actual development of region and the situational and developmental objectives needed. However, the difficulty facing the situational planning is in selecting one of these alternatives to be the best in order to make a balanced situational re-structure, and achieving the economic, social and civil objectives. The developmental situation elements in the regions and governorates, including (Karbala) impose themselves as situational power which implies the process of re-structural arrangement where the situational development is considered the active method for such arrangement. Thus, the difficulty of making decision in selecting any of the developmental alternatives seems easier for the situational planner as he has the programming methods and operations researches. The scientific method is used for making decision to suggest the developmental alternative which can achieve the strategic comprehension of the development elements and ensures the exploitation better to achieve the decree objectives.  The method of decisions making theory is considered one scientific method which can be used in this regard. They mechanism of the decisions theory implies making more than one alternative to arrange the strategies and objectives in a matrix through which can make more than a case of making decision towards selecting the suitable situational  strategy to achieve the objectives under the case of making decision brunt determined by the interdependent aspect in making decision. This necessitates knowledge of the developmental reality of the studied region or province. Therefore, the applied study of the developmental reality in the Karbala (region) province showed that there are two strategies that can be adopted to bring about spatial development in that province: the balanced growth strategy in the first, rational aspect drawn for sectors for development and the decision to maximize returns, and in the second aspect (cumulative) and the third (participatory), as well as the application proved the possibility of adopting the strategy of manufacturing and manufacturing for export in order to achieve a special type of goals at the lowest costs, whether in the case of certainty or risk, and this leaves the room clear for the decision maker to adopt any of the two strategies.